Consequences of interspecific hybridization and virus infection on the growth and fecundity of three threatened coastal Lepidium (Brassicaceae) species from New Zealand. (7th April 2015) - Van Vianen, Josh C. C. M.; Houliston, Gary J.; Fletcher, John D.; Heenan, Peter B.; Chapman, Hazel M.
Abstract L epidium castellanum, L. juvencum and L. oleraceum are threatened coastal cresses endemic to New Zealand. These three species were selfed and interspecific hybrids generated for examination of hybrid fitness and inbreeding depression. In controlled glasshouse experiments, the interspecific hybrids and selfed progeny were inoculated with a strain of the introduced Turnip mosaic virus (TuMV) previously isolated from wild populations of L. aegrum. Experiments tested the hypothesis that heterosis in the interspecific hybrids provides a gain in TuMV resistance in comparison to selfed plants. We show that interspecific hybrids of three genetically distinct species of Lepidium increased plant performance and reduced susceptibility to the effects of the TuMV. We suggest that interspecific hybridization could be implemented as a conservation management strategy and that a broader outlook may be required to mitigate the negative impacts of introduced pathogens on threatened species.